"O sagrado direito de liberdade" : experiências de escravos nos tribunais da comarca de Estância/Sergipe (1871-1888) - Santos, Moisés Augustinho dos (2017)
This study, grounded in the social history of E. P. Thompson (1997; 1998) and in the micro-history of Ginzburg (2011; 2014), identifies and discusses social and cultural meanings from individual and collective trajectories of subjects that participated in the historical process of slavery in Brazil. In order to understand the expectations of the slaves and their trustees when trying to gain freedom through an appeal to justice, it investigates aspects of the application of the provisions of law, the positions of judges, lawyers, trustees, custodians, experts and arbitrators, that, through their actions influenced directly or indirectly in the destinations of the slaves, and reveals networks of solidarity between free men and slaves, questioning the positions of lawyers, judges and public officials in the face of judicial disputes of slaves applying for freedom in the absence of their owners. The temporal cut corresponds to the sources analyzed, namely, the promulgation of the Law of Ventre Livre, in 1871, which resulted in significant changes in the relations between masters and slaves, until the abolition of slavery, in 1888.